Theories of International Relations and the Fluidity of the International Political System - Onwutuebe, Chidiebere J. (Journal of Contemporary International Relations and Diplomacy, 2022)
The international political system continues to undergo varying degrees of permutation which often beckon the need to (re)appraise, contest, revise and reposition hitherto existing theories of international relations with a view to achieving relative precision in the analysis of global events. Recent developments in the international political system resonate and validate the fluidity and evolving nature of theories of international relations as tools required to describe, explain, analyse and predict global trends. This study underscores the place and role of prevailing global forces in shaping the nature, direction and character of theories of international relations. It demonstrated ways in which centripetal and centrifugal subtleties of the international system orchestrate new political thoughts and search for more apposite theoretical frameworks necessary to capture the exigencies of emerging world realties. Secondary data and descriptive method of analyses were used in the study. The study showed that regardless of the usefulness of theories of international relations in creating relevant links necessary to explain observable scenarios in the global arena, their importance resides largely in their capacity to reasonably account for global actions, behaviours and events irrespective of differences in historical time boundaries as well as variations in geographies. In conclusion, the study stressed the susceptibility of theories of international relations to vagaries of an ever-evolving international system majorly characterized by trends in peace and war, cooperation and conflicts, conflictual national foreign policy objectives as well as general interest of states and non-state actors.